Periodic solutions for systems of functional-differential semilinear equations at resonance - Amster, Pablo; Epstein, Julián; Sanjuán Cuéllar, Arturo (Topological Methods in Nonlinear Analysis, 2021)
Motivated by Lazer-Leach type results, we study the existence of periodic solutions for systems of functional-differential equations at resonance with an arbitraryeven-dimensional kernel and linear deviating terms involving a general delayof the form $\int_0^{2π}u(t+s)dλ(s)$, where $λ$ is a finite regular signed measure. Our main technique shall be the Coincidence Degree Theorem due to Mawhin.